1992
DOI: 10.1172/jci115704
|View full text |Cite
|
Sign up to set email alerts
|

Association of polar amino acids at position 26 of the HLA-DQB1 first domain with the anticentromere autoantibody response in systemic sclerosis (scleroderma).

Abstract: HLA class II alleles (detected by DNA typing) were determined in 116 Caucasians with systemic sclerosis positive and negative for anticentromere autoantibodies (ACA). Significantly increased frequencies of HLA-DR5(DRw11) (P = 0.009) and the Dw13(DRB1*0403, *0407) subtypes of DR4 (probability corrected, Pc = 0.005) were seen in ACA positive patients, and HLA-DR1 and DRw8 were also increased. These findings appeared to reflect linkage disequilibrium of DR5(DRwll) and many DR4(Dw13) haplotypes with HLADQw7 and DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 42 publications
(26 reference statements)
8
34
2
1
Order By: Relevance
“…Tyrosine at position 26 in the DQB1 (31 domain was also shown to be one of the amino acid residues associated with another SSc-specific autoantibody, anticentromere (53). Thus, it appears that the putative antigen binding cleft at position 26 in the DQB1 31 outermost domain is important for these two autoantibody production, and different HLA-DR genes define the reactivity to the two different antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine at position 26 in the DQB1 (31 domain was also shown to be one of the amino acid residues associated with another SSc-specific autoantibody, anticentromere (53). Thus, it appears that the putative antigen binding cleft at position 26 in the DQB1 31 outermost domain is important for these two autoantibody production, and different HLA-DR genes define the reactivity to the two different antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The ACA response has been associated with HLA-DQBl*O5 alleles (48,49), and less commonly with DQBl*O301 and DQBl*O401 or "0402 (48). All of these ACA-associated DQBl alleles possess nonpolar amino acid residues (glycine or tyrosine as opposed to leucine) in position 26 of their outermost domains.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that ACApositive PSS patients were considered separately because ofthe association of this autoantibody response also with HLA-DQB 1 *0301 (DQw7) (37) (Table III).…”
Section: Scleroderma-related Autoantibody Frequencies Of the 132mentioning
confidence: 99%
“…Using restriction fragment length polymorphisms (RFLPs) and oligonucleotide typing of class II MHC alleles, we have reported recently that HLA-DQB1 alleles possessing a polar amino acid (either tyrosine or glycine) at position 26 of the outermost domain constitute the strongest association with the ACA autoimmune response in PSS patients (37). In the present study, we used the same techniques in a large number of PSS patients to compare HLA-DRB1, DRB3, DQA1, and DQB 1 alleles in antitopo I-positive and -negative PSS patients and controls to show that the antitopo I response also is correlated most closely with specific HLA-DQB 1 from Miami, as well as 9 from Georgia who were part of an epidemiological study reported previously (38 Genetic analysis ofHLA-DRBI, DRB3, DQAJ, and DQBI alleles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation